Effects of Modified Magnetic Field on Unsteady Flow of Viscoelastic Stratified Fluid Between Two Parallel Inclined Riga Plates with Viscous Dissipation - Oluwafemi Waheed, Lawal (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study in this paper investigates the effect of modified magnetic field on unsteady flow of viscoelastic stratified fluid between two parallel Riga plates inclined at an angle. The magnetic field is generated by the upper and lower Riga plates which are kept stationary. These Riga plates are kept at different temperature which decay with time with fluid density and viscosity are considered to be variable among different layers within the medium. The non-linear PDEs that govern the flow problem are transformed into non-dimensional PDEs and solved numerically using explicit finite difference scheme. Maple 23 is used to implement and simulate these schemes and the result are analyzed and presented inform of graphs. It is established that the effect of Reynolds number, viscoelastic parameter, stratification parameter and Prandtl number on the velocity and temperature distribution are subdued by modified magnetic field.